Purification and characterization of mannitol dehydrogenase from the fungal tomato pathogen Cladosporium fulvum (syn. Fulvia fulva) - Noeldner, P.; Coleman, M.; Faulks, R.; Oliver, Richard (1994)
As part of our studies to elucidate the mechanisms by which biotrophic plant pathogens obtain and retain carbon from their plant hosts, we have investigated the properties of the mannitol dehydrogenase (E.C. 1.1.1.67) of Cladosporium fulvum (syn. Fulvia fulva). The enzyme has been purified to near-homogeneity and has a subunit mol. wt of 29 kDa and is probably tetrameric. The Michaelis-Menten constants for mannitol and fructose are high and the equilibrium constant lies towards mannitol accumulation. A β-fructosidase (invertase) activity was detected and found to be largely wall-bound. The properties of these enzymes are consistent with a role in the hydrolysis of photosynthetically produced sucrose and the accumulation of mannitol as a storage compound during fungal growth in the plant.